Analysis Of Criminal Law Respect for Deceased Persons - Isnawan, Fuadi (Al-Jinayah : Jurnal Hukum Pidana Islam, 2024)
Respect for individual rights is an important moral and legal foundation in maintaining justice and humanity in the criminal law system. Although the individual has passed away, complexities arise as their rights still need to be respected. A deceased individual's legacy, including reputation and social influence, remains relevant and influences society. This research aims to understand how the criminal law system, particularly in the Criminal Code (KUHP), handles cases involving deceased individuals, including the protection of their reputation and open legal liability. This research utilizes a normative legal research method that involves analyzing existing legal norms. The results show that the Indonesian criminal law in detail regulates respect for deceased individuals in the Criminal Code. Despite having physically left the world, the law still recognizes and protects their rights regarding honor, reputation, and inheritance. Crimes against corpses are regulated in Chapter V of the Second Book of the Criminal Code on Crimes Against Public Order. Articles in the Criminal Code, such as Articles 175, 178, 179, 180, 181, 320, and 321, provide protection to the reputation, burial, graves, corpses, as well as preventing insults or defamation of deceased individuals, punishable by imprisonment or fines. Although the individual has biologically left the world, the law still recognizes and protects their rights regarding honor, reputation, and inheritance. Chapter V of the Second Book of the Criminal Code regulates crimes against public order involving corpses. Articles such as Article 175 to Article 321 provide protection to reputation, burial, graves, and corpses, and prevent insult or defamation of deceased individuals, punishable by imprisonment or a fine.